Does it matter if clinicians recruiting for a trial don't understand what the trial is really about? Qualitative study of surgeons' experiences of participation in a pragmatic multi-centre RCT. - Ziebland, S; Featherstone, K; Snowdon, C; Barker, K; Frost, H; Fairbank, J (2007)
BACKGROUND: Qualitative methods are increasingly used to study the process of clinical trials and patients understanding of the rationale for trials, randomisation and reasons for taking part or refusing. Patients' understandings are inevitably influenced by the recruiting clinician's understanding of the trial, yet relatively little qualitative work has explored clinicians' perceptions and understandings of trials. This study interviewed surgeons shortly after the multi-centre, pragmatic RCT in which they had participated had been completed. METHODS: We used in-depth interviews with surgeons who participated in the Spine Stabilisation Trial (a pragmatic RCT) to explore their understanding of the trial purpose and how this understanding had influenced their recruitment procedures and interpretation of the results. A purposive sample of eleven participating surgeons was chosen from 8 of the 15 UK trial centres. RESULTS: Although the surgeons thought that the trial was addressing an important question there was little agreement about what this question was: although it was a trial of 'equivalent' treatments, some thought that it was a trial of surgery, others a trial of rehabilitation and others that it was exploring what to do with patients in whom all other treatment options had been unsuccessful. The surgeons we interviewed were not aware of the rationale for the pragmatic inclusion criteria and nearly all were completely baffled about the meaning of 'equipoise'. Misunderstandings about the entry criteria were an important source of confusion about the results and led to reluctance to apply the results to their own practice. CONCLUSION: The study suggests several lessons for the conduct of future multi-centre trials. Recruiting surgeons (and other clinicians) may not be familiar with the rationale for pragmatic designs and may need to be regularly reminded about the purpose during the study. Reassurance may be necessary that a pragmatic design is not considered a design fault. We conclude that it does matter if clinicians do not understand the rationale for the trial if, as we have shown here, their perception of the trial aims and methods adversely affects who they recruit; if their views affect what the patients are told; and if they mistakenly view the results as unscientific, unreliable and ultimately irrelevant to their practice.